Anesthesia of a patient with congenital cataract, facial dysmorphism, and neuropathy syndrome for posterior scoliosis: A case report - Hudec, Jan; Kosinova, Martina; Prokopova, Tereza; Filipovic, Milan; Repko, Martin; Stourac, Petr (World journal of clinical cases, 2022)
BACKGROUND: Congenital cataract, facial dysmorphism, and neuropathy (CCFDN) syndrome is an extremely rare multiorgan disorder. Characteristics include congenital cataracts, facial deformation, extremity deformities, and demyelinating neuropathy. CCFDN syndrome is associated with increased risk during anesthesia including rhabdomyolysis or epileptic seizures. There is a lack of published information about difficult airways in these patients. Difficult airways during intubation represent one of the most dreaded anesthesia complications: A "can not intubate, can not oxygenate" scenario. Presented herein is the first described successful endotracheal intubation of a CCFDN syndrome patient. CASE SUMMARY: We report the anesthetic management of a 13-year-old girl with CCFDN syndrome scheduled for posterior neuromuscular scoliosis correction surgery. The patient suffered from extensive progressive neuromuscular scoliosis with a Cobb angle of 83°. Her limitations included neuropathy and a scoliotic curve. This condition negatively impacted her quality of life. This case reflects the potential anesthetic complications for posterior scoliosis correction and CCFDN syndrome. The challenge for our anesthetic team was the limited amount of data about anesthetic management of this condition. In total, one case report without any data about endotracheal intubation of patients with this condition was available. Endotracheal intubation in our case was uncomplicated. Another focus of our case was the prevention of possible complications associated with this syndrome, including rhabdomyolysis and seizures. Rhabdomyolysis can be triggered by some types of anesthetic agents like suxamethonium or volatile anesthetics, especially in patients with certain types of myopathies. CONCLUSION: Adequate understanding of the anesthetic management of CCFDN syndrome can reduce perioperative complications and improve patient outcome after surgery.